2020
DOI: 10.1111/apa.15514
|View full text |Cite
|
Sign up to set email alerts
|

Point‐of‐Care test screening versus Case finding for paediatric coeliac disease: A pragmatic study in primary care

Abstract: In paediatric coeliac disease (CD), symptoms may not be a reliable factor in the diagnosis of coeliac disease as described by Rosen et al, 1 and thus, recommendations for reviewing CD screening criteria were suggested. 2 Apart from the costs, an important limiting factor in paediatric population mass screening using conventional immunoglobulin (Ig) A tissue transglutaminase (tTGIgA) may be the low compliance of asymptomatic children to be referred for testing. On the other hand, the alternative approach, the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…The results from the latter were coupled with an avant-garde CDSS system to define a strategy for making the diagnosis easier, less invasive, and feasible. Moreover, this project's exploration of the hypothetical deep roots of the "coeliac iceberg" has been made possible, uncovering many disorders that may be prevented by recognizing a pathogenetic relationship with gluten [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results from the latter were coupled with an avant-garde CDSS system to define a strategy for making the diagnosis easier, less invasive, and feasible. Moreover, this project's exploration of the hypothetical deep roots of the "coeliac iceberg" has been made possible, uncovering many disorders that may be prevented by recognizing a pathogenetic relationship with gluten [14].…”
Section: Discussionmentioning
confidence: 99%
“…A different approach by Meijer-Boekel et al [13] performed a case finding project to detect CD children who visit the Youth Health Care Centres in the Netherlands to evaluate whether it is feasible, cost-effective, and well accepted by the population [13]. A study compared these two different approaches and concluded that a mass screening through POCT seemed more convenient than a case finding strategy, based on symptoms, that otherwise can miss asymptomatic children [14]. For optimal results as a screening tool, the POCT must have a high negative-predictive value in order to avoid missing cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade, several POCTs detecting mostly anti-tTG IgA have been developed, but their role remains unclear in clinical practice either as a mass screening tool or, in a case-finding strategy, as a first-line instrument to be used in at-risk individuals before the use of conventional serology. [12][13][14][15][16][17] Previous studies have shown variable sensitivity or specificity of these tests compared with the conventional serology, even if a recent systematic review and meta-analysis reported a high pooled sensitivity and specificity of POCTs in diagnosing CD (94% and 94.4%, respectively). 18 The primary aim of this study was to assess the diagnostic accuracy of a novel anti-tTG IgA/anti-DGP IgG-based POCT, compared with conventional serology (reference) methods in people with CD or suspected for CD.…”
Section: Introductionmentioning
confidence: 99%